Structure of certain classes of groups with locally cyclic Abelian subgroups - Kuzennyi, N. F.; Maznichenko, S. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We investigate groups with locally cyclic Abelian subgroups. We give a constructive description of locally solvable groups of this type that contain a nonidentity periodic part; we also describe locally solvable groups all Abelian subgroups of which are cyclic.